(untitled) (Experimental biology, 2015)
The article presents the results of work on obtaining the sorghum-sudangrassheterotic hybrids for the southeastern Kazakhstan conditions. The biological characteristics of sweet sorghum and Sudan grass varieties were determined in the work. High-sugar forms of sorghum reciprocally crossed with sudan grass. In various combinations the set of seed ranged from 3 to 21 percent. 237 hybrid seeds were obtained.